MULTICULTURALISM: DYNAMICS OF TRADITIONAL COMMUNITY DISTRICTS TO CREATIVE CULTURAL ROUTES FOR LEARNING MEDIA: A CASE STUDY OF BANGPHO, BANG SUE DISTRICT, BANGKOK - Tumkosit, Manintra; Pangkesorn, Anucha (Journal of MCU Nakhondhat, 2024)
This research article aims 1) To investigate the history and development of the Bang Pho area to comprehend its value; 2) To explore the social conditions from the past to the present to understand the society and coexistence within the Bang Pho community; and 3) To design a cultural pathway presented through media that aligns with the current context and informs policy. This qualitative research employs document review, interviews, and focus group discussions with residents of Bang Pho, entrepreneurs, urban development agencies, and academics. The research employs content analysis to interpret the data. The findings reveal that the cultural value of the Bang Pho area encompasses both tangible and intangible cultural elements. Physical changes in the area are primarily influenced by traffic routes, which affect settlement patterns. The social characteristics of Bang Pho reflect a multicultural society where people of various nationalities have coexisted since the beginning of the Rattanakosin period, resulting in cultural diversity that remains a distinctive feature today. This diversity is evident in the local food, beliefs, and carpentry traditions. The study suggests that the conservation approach should emphasize the value of Bang Pho as a cultural tourism resource. The media development strategy should convey the cultural value through a cultural map and a multicultural identity route in the Bang Pho area using brochures and multimedia. This approach includes the four processes of the MAPS model: 1) Multicultural routes: creating a community map, 2) Activity: organizing activities with community participation, 3) Public Relations: conducting public relations campaigns, and 4) Storytelling: presenting stories from memories and experiences, disseminated via social media. This format is deemed appropriate for the current context.